How PV systems can be cost-competitive for mobile BTS in remote areas of Algeria - Hamza Siyoucef; Benameur Afif; Amina Benhammou; Boualem Merabet (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
Solar electricity for telecom infrastructure has became one of the main contributors of electrical energy to the energy system in the future, but solar technology needs support to find its way to the market. Since photovoltaic (PV) electricity always involves  very high costs compared to electricity from other sources, a striking question is: how can PVs achieve competitiveness? There are  different strategies for promoting applied PV electricity generation around the world. Here, we simulated and designed a 40 KWp injected PV power, to evaluate the energy of the incident photon flux, that produced by PV panels and the energy injected into the electricity grid, and judge whether the installation is profitable, and if the technology is economical. The results reveal that the site of Tamanrasset (in the extreme south of Algeria) could produce an annual energy production 73879 kWh, which justify the reason the German Academy has chosen such site for the famous desert project, lastly launched between the two countries.